Sellar Tuberculosis Mimicking Pituitary Adenoma - Maharjan, S.; Satyal, B.; Baidya, R. (Kathmandu University Medical Journal, 2022)
Tuberculosis of central nervous system accounts for only 1% of tuberculosis cases worldwide, of which pituitary is an extremely unusual site. We report a case of pituitary tuberculosis in a 29-year-old female presenting with complains of headache and diminished vision on right eye. It was misdiagnosed as pituitary adenoma on radiology. Biopsy showed epithelioid granulomas, langhans giant cells and caseous necrosis. Ziehl nelseen stain showed presence of acid fast bacilli confirming the tubercular etiology. Therefore, histology remains the mainstay for diagnosis of these lesions. Early diagnosis and prompt use of antitubercular drugs results in good outcome.